Ten new records of Polystichum (Dryopteridaceae) for Vietnam and lectotypification of Polystichum atroviridissimum and P. fimbriatum - Lu, Ngan Thi; Zhang, Liang; Zhang, Li-Bing (Phytotaxa, 2014)
Ten new records of Polystichum (Dryopteridaceae; pteridophyta) for Vietnam, P. auriculum, P. dangii, P. excellens, P. fimbriatum, P. liboense, P. minimum, P. mucronifolium, P. nepalense, P. subacutidens, and P. xichouense, are reported from new collections, incorrectly attributed past collections, or unidentified material. Color images are provided for newly collected species. Type information is given for all related names. We also lectotypified two names of Polystichum: P. atroviridissimum and P. fimbriatum.